2020
DOI: 10.1007/s10340-020-01302-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of entomopathogenic fungi introduced as corn endophytes on the development, reproduction, and food preference of the invasive fall armyworm Spodoptera frugiperda

Abstract: Fall armyworm (FAW), Spodoptera frugiperda, is a migratory polyphagous pest that causes major damage to economically important cultivated grasses, such as corn. Native to the neotropics in America but recently reported as an invasive pest in Africa and Asia, FAW imposes a serious threat to food security and sustainable crop productivity due to lack of effective management. In this study, the introduction of entomopathogenic fungi as endophytes was explored as an alternative more sustainable management strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 42 publications
8
80
3
1
Order By: Relevance
“…In the laminar airflow cabinet, the plant roots were cut to a size of 0.5 cm x 0.5 cm, then the surface was sterilized, modifying the method of Elfita et al (2019) by immersing plant tissue in 70% EtOH (Ethyl alcohol) for 2 minutes, then dipping it in 1% NaOCl (Sodium hypochlorite) for 1 minute, then rinsed three times in the sterile distilled water for 1 minute. To determine the success of this surface sterilization, the last rinse was grown onto Potato Dextrose Agar (PDA) which modified the method of Russo et al (2020). If the PDA media did not grow the microorganisms, it meant that the surface sterilization was successful (Ramirez-Rodriguez and Sánchez-Peña 2016).…”
Section: Exploration Isolation and Purification Of Endophytic Fungusmentioning
confidence: 99%
See 1 more Smart Citation
“…In the laminar airflow cabinet, the plant roots were cut to a size of 0.5 cm x 0.5 cm, then the surface was sterilized, modifying the method of Elfita et al (2019) by immersing plant tissue in 70% EtOH (Ethyl alcohol) for 2 minutes, then dipping it in 1% NaOCl (Sodium hypochlorite) for 1 minute, then rinsed three times in the sterile distilled water for 1 minute. To determine the success of this surface sterilization, the last rinse was grown onto Potato Dextrose Agar (PDA) which modified the method of Russo et al (2020). If the PDA media did not grow the microorganisms, it meant that the surface sterilization was successful (Ramirez-Rodriguez and Sánchez-Peña 2016).…”
Section: Exploration Isolation and Purification Of Endophytic Fungusmentioning
confidence: 99%
“…In the field, the S. frugiperda larvae were found appearing on leaf surfaces from 6.30 a.m. to 8.00 a.m. To control the larvae of S. frugiperda, it is more effective to use an endophytic entomopathogenic fungus because the endophytic fungi are those that systemically colonize host plant tissues, associating mutually, and without being pathogenic to the host plants (Lira et al 2020;Kasambala et al 2018). The endophytic fungus has many advantages, apart from having a mode of action through stomach poison (Russo et al 2020), it can also kill by contact (Ramirez-Rodriguez and Sánchez-Peña 2016), and it can also stimulate plant growth (Jaber and Ownley 2018;Ahmad et al 2020;Bamisile et al 2020;Barra-Bucarei et al 2020). The endophytic fungi pathogenic to S. frugiperda larvae need to be found from maize and other plant tissues in Indonesia, especially in South Sumatra and are expected to be potential alternatives to the use of synthetic insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…The endophytic fungi can still be found on roots, stems, and leaves of tomato up to 30 days after inoculation (Carolina et al 2020). Endophytic B. bassiana colonized 100% of leaves, 80% of stems, and 60% of roots of maize 7 days after foliar spray and caused significant reductions in S. frugiperda growth and reproduction (Russo et al 2020). The research results of Shikano (2018) showed the endophytic fungi were able to live in the tissue for several months depending on the age of the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the plant parts were surface sterilized using the method of Elfita et al ( 2019) with 70% EtOH (ethyl alcohol) and 1% NaOCl (sodium hypochlorite) and then rinsed 3 times. The last rinse water was used to check whether the microorganisms causing surface contamination were still present and carried out by growing them onto sabouraud dextrose agar (SDA) (Russo et al 2020). Obtaining the endophytic fungi isolates started with growing the plant parts that sterilized earlier onto a media.…”
Section: Exploration Isolation and Purification Of Fungimentioning
confidence: 99%
“…EPF can mediate the interactions of insects with their host plants in several ways, such as mediating herbivory (Rondot and Reineke 2018;Russo et al 2020) and oviposition behavior (Jaber and Araj 2018). For example, EPF can alleviate feeding of aphids for inoculated maize plants (Mahmood et al 2019), but bene ting parasitoids (González-Mas et al 2019).…”
Section: Introductionmentioning
confidence: 99%